2022
DOI: 10.1111/hiv.13312
|View full text |Cite
|
Sign up to set email alerts
|

People with HIV have a higher risk of COVID‐19 diagnosis but similar outcomes to the general population

Abstract: Background We investigated the effect of HIV on COVID‐19 outcomes with attention to selection bias due to differential testing and comorbidity burden. Methods This was a retrospective cohort analysis using four hierarchical outcomes: positive SARS‐CoV‐2 test, COVID‐19 hospitalization, intensive care unit (ICU) admission and hospital mortality. The effect of HIV status was assessed using traditional covariate‐adjusted, inverse probability‐weighted (IPW) analysis based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In a population-based study from the Western Cape Province, South Africa, which included 540,552 PLWH, the cumulative incidence of SARS-CoV-2 infection through June 9, 2020, was similar by HIV status (0.74% vs. 0.63%) [35]. Cohorts from large health systems have instead been more mixed, with higher incidence of COVID-19 with the University of California, San Diego health system [40], and Kaiser Permanente Southern California [41], but similar incidence within the U.S. Veteran Administration Veterans Aging Cohort [38] and the San Francisco Department of Public Health Clinics [36].…”
Section: Susceptibility To Sars-cov-2 Infection Among Plwh In Populat...mentioning
confidence: 99%
“…In a population-based study from the Western Cape Province, South Africa, which included 540,552 PLWH, the cumulative incidence of SARS-CoV-2 infection through June 9, 2020, was similar by HIV status (0.74% vs. 0.63%) [35]. Cohorts from large health systems have instead been more mixed, with higher incidence of COVID-19 with the University of California, San Diego health system [40], and Kaiser Permanente Southern California [41], but similar incidence within the U.S. Veteran Administration Veterans Aging Cohort [38] and the San Francisco Department of Public Health Clinics [36].…”
Section: Susceptibility To Sars-cov-2 Infection Among Plwh In Populat...mentioning
confidence: 99%
“…This study also lacked data regarding smoking status, although this was partly compensated by adjusting for chronic lung disease. Given that our study population only includes hospitalized people, we could not assess factors influencing the risk of hospitalization, for example higher test probability for SARS-CoV-2 for PWH, which has been shown in a recent report from the US [26]. It is also possible that restricting the population to hospitalized people introduces collider bias, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although no clinical evidence demonstrates the higher prevalence of COVID-19 or COVID-19 diagnosis rate in PLWH than in the general population, [9,27–30] more studies in large-scale population suggested that PLWH might have increased risk of COVID-19–related hospitalization or death than healthy individuals. [28,29,31–36] Residual inflammation and immune activation even after successful ART, as well as the high rate of comorbidities in PLWH, might result in poor COVID-19 outcomes.…”
Section: Sars-cov-2 Coinfection In Plwhmentioning
confidence: 99%